2018
DOI: 10.1111/phpp.12418
|View full text |Cite
|
Sign up to set email alerts
|

The “Enseki” sandbath: A novel, safe and effective far‐infrared bathing procedure for health

Abstract: We concluded that the Enseki method is a safe and well-tolerated FIR bathing procedure for regeneration and relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The IR saunas (and similarly to them the Waon therapy and the Enseki sandbath), but also the IR sauna blankets, have been shown to have a general detoxifying effect and to reduce fatigue in athletes and improve muscle recovery after training sessions [24,25]. In addition, they have a general relaxation effect.…”
Section: Non-invasive Aesthetic Medicine and Beauty Carementioning
confidence: 99%
“…The IR saunas (and similarly to them the Waon therapy and the Enseki sandbath), but also the IR sauna blankets, have been shown to have a general detoxifying effect and to reduce fatigue in athletes and improve muscle recovery after training sessions [24,25]. In addition, they have a general relaxation effect.…”
Section: Non-invasive Aesthetic Medicine and Beauty Carementioning
confidence: 99%
“…Consequently, it appeared that Enseki method was, at least, no negative impact on human health. Biochemical analysis was also performed including blood glucose, HbA1c, uric acid, lactate, fatty acid and others, demonstrating no abnormal score [11]. Finally, results of questionnaires demonstrated that 90% of the participants answered the comfort and wished to further repeat the bathing [11].…”
Section: Introductionmentioning
confidence: 99%
“…The second is an FIR dry sauna in which light is used to create heat and directly irradiate the target (indeed, skin) [10]. In 'Enseki' sandbath, a novel FIR sauna system our team reported recently, ceramic beads were filled in a bathtub equipped with computerized hot water circulating system and heated at up to 50 ℃ [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, they are used in various fields such as animals [2,3], agriculture [4], buildings [5] and humans. For example, thermal cameras are applied to humans for anomaly detection such as heatstroke [6] and infection [7]. Human skin temperature is also used for estimating various psychological states such as stress and thermal comfort [8,9,10].…”
Section: Introductionmentioning
confidence: 99%